Association of Paraoxonase 1 Gene Polymorphisms With the Risk of Hepatitis B Virus-related Liver Diseases in a Guangxi Population: A Case-control Study. Issue 48 (December 2015) - Lao, Xianjun; Wang, Xiaogang; Liu, Yanqiong; Lu, Yu; Yang, Dongmei; Liu, Minyan; Zhang, Xiaolian; Rong, Chengzhi; Qin, Xue; Li, Shan
Abstract : Abstract: Paraoxonase 1 (PON1), a liver-induced glycoprotein enzyme responsible for antioxidant defense against reactive oxygen species and anti-inflammatory, has been linked to various cancers. The objective of this study was to explore the association of PON1 rs662 and rs705382 with the risk of chronic hepatitis B (CHB), hepatitis B virus-related liver cirrhosis (LC), and hepatocellular carcinoma (HCC) in patients living in the Guangxi region of southern China. The PON1 rs662 and rs705382 single-nucleotide polymorphisms (SNPs) were genotyped by polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) in 99 CHB patients, 84 LC patients, 258 HCC patients, and 221 healthy controls. Significant associations with CHB risk were observed for the rs705382 SNP after adjusting for sex, age, ethnicity, smoking, alcohol consumption, and body mass index. When stratified by sex and age, this positive association was significantly strengthened among men and individuals over 40 years old. Moreover, a decreased risk of LC was associated with the rs705382 CG and the combined GG + CG genotypes among women, with borderline statistical significance. In haplotype analyses, the haplotype GA was associated with a 1.68-fold increase in the risk of HCC. Our results showed that the PON1 rs705382 SNP might be a risk factor for CHB in Guangxi populations.